RAB5A Promotes Active Fluid Wetting by Reprogramming Breast Cancer Spheroid Mechanics - Lemahieu, Grégoire; Moreno-Layseca, Paulina; Hub, Tobias; Bevilacqua, Carlo; Gómez-González, Manuel; Pennarola, Federica; Colombo, Federico; Massey, Andrew E.; Barzaghi, Leonardo; Palamidessi, Andrea; Homagk, Leon-Luca; Barnett, Samuel F. H.; et al. (Advanced science, 2025)
Unjamming transitions from a solid-like to a fluid-like state are a gateway to breast epithelial cancer invasion. However, the mechanical interplay between phase transitions and dimension transitions, in particular wetting, remains elusive, despite being critical for understanding the onset of metastatic dissemination. This study shows that unjamming, mediated by the RAB5A GTPase, alters carcinoma spheroid fluidity, rigidity, and rewires adhesion mechanics to drive supracellular active wetting as a new mode of tumor expansion. Spheroid fluidification enhances the selective expression of integrin subunits and increases focal adhesion dynamics, inducing a fluid-like spreading behavior on specific matrix ligands. Notably, nanoscale regulation of integrin clustering can select for distinct phase transitions at the collective scale upon wetting. In this framework, fluidized spheroids polarize into cohesive “supracells”, and maintain a stiff peripheral actin bundle as measured by nanomechanical mapping. Furthermore, a combination of Brillouin microscopy and 2.5D traction force analysis reveals a mechanical switch within the spheroid core, characterized by significant cell softening and a reduction in compressive forces exerted on the substrate, thereby mimicking the wetting of a liquid droplet. These findings establish unjamming-driven active wetting as a key mechanism to comprehend the molecular and biophysical underpinnings of solid tumor invasion.
Online verfügbar: 25. Juli 2025
Gesehen am 16.12.2025